ANALYSIS INFLUENCE OF EFFECTIVENESS AND EFFICIENCY LOCAL ORIGINAL INCOME ON REGIONAL FINANCIAL INDEPENDENCE IN MAPPI REGENCY - Valentino Febrian Legoh; Heffi Christya Rahayu; Ira Geraldina (Transpublika Publisher, 2024)
The regional autonomy in Mappi Regency shows a need for good governance, especially in financial management. The government is trying to increase financial independence, but still relies heavily on the central government. This highlights difficulties in generating enough revenue and managing the budget effectively. This study was conducted with the aim of discussing the Influence of the Effectiveness and Efficiency of Local Original Revenue on Regional Financial Independence in Mappi Regency. The method used is a quantitative approach. The population of this research is financial reports Mappi District Regional Government complete from 2014 to 2023. The sampling technique used is purposive sampling. This study was designed with a causality method because it seeks the influence of cause and effect of several variables developed from a theory. Furthermore, it was analyzed using the Structural Equation Modeling (SEM) technique. The results of this study indicate that regional tax efficiency has a positive impact on Locally-generated revenue, The effectiveness of regional taxes has a positive impact on Locally-generated revenue, Locally-generated revenue has a positive impact on Regional Independence, Regional tax efficiency has a positive impact on Regional Independence through Locally-generated revenue as a mediating variable, the effectiveness of regional taxes has a positive impact on regional independence through Locally-generated revenue as a mediating variable. The Mappi Regency Regional Government should focus on managing their budget to improve community welfare, which will ultimately lead to increased regional independence. A prosperous community will boost economic growth and generate more revenue locally.